2015
DOI: 10.4236/ojgas.2015.59020
|View full text |Cite
|
Sign up to set email alerts
|

Value of Different Diagnostic Markers in Spontaneous Bacterial Peritonitis in HCV Egyptian Cirrhotic Patients

Abstract: Background: Spontaneous bacterial peritonitis (SBP) is a life-threatening infection occurring in 8% -30% of ascitic cirrhotic patients; different laboratory diagnostics play a pivotal role for rapid and effective management of SBP patients. Polymorphonuclear leucocytic (PMNLs) count in Ascitic fluid (AF) is the mainstay for the diagnosis, whereas the diagnostic role of alternative biomarkers is rather controversial. In many studies, serum lipopolysaccharide binding protein (LBP) was elevated and Complement 3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…Other biochemical findings in AF analysis confirmed the presence of infection like high LDH and low glucose. These findings were in accordance with that of Badawy et al [34] and EL-Motasem et al [35].…”
Section: Discussionsupporting
confidence: 93%
“…Other biochemical findings in AF analysis confirmed the presence of infection like high LDH and low glucose. These findings were in accordance with that of Badawy et al [34] and EL-Motasem et al [35].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, Disturbed conscious level, abdominal pain, fever and abdominal enlargement were the main clinical presentation in SBP patients (34,4 %, 21% , 18.8% and 15.6% respectively). This result was in agreement with El Motasem et al 19 As regard routine laboratory findings of the current study, it showed no significant statistical difference between both groups except for TLC in blood, PMN, platelets indices (MPV and PDW) and serum Na. These results were in agreement with Khorshed et al 7. In our study, CRP in blood with ESR levels were elevated in SBP group with high statistical significant difference (p<0.001) among both groups that agreed with Awad et al 20, this explained by activation of cytokine synthesis in response to circulating bacterial endotoxins as reported by El sadek et al, 21 .…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, none of ascitic samples of SBP group were culture positive [30]. This variation in isolation rates is mainly due to the relatively low concentration of bacteria in AF [31] as colony count in spontaneously infected ascites is approximately one microorganism per mL [28]. Additionally, discrepancies of culture results may be due to difference in culture techniques as some studies didn't use blood culture bottles [32].…”
Section: Roc Curve Of Ascites Ngal For Diagnosis Of Ascitic Fluid Infectionmentioning
confidence: 99%